Criminality of Child Involvement in Prostitution thru Online Media: Educational Study and Prevention Efforts - Fita Fitriana Parwahadi; M. Syahrul Borman; Irawan Soerodjo (Journal of Practice Learning and Educational Development, 2026)
This research examines the legal consequences for perpetrators of online prostitution involving minors and analyzes legal protections for children as victims and offenders. The online prostitution phenomenon is increasingly alarming, with minors becoming subjects of covert yet widespread sexual exploitation. This study employs a normative juridical method using statute, conceptual, and case approaches. Based on analysis of legislation and court rulings, pimps and service users are subject to strict criminal sanctions, while child offenders are processed through the juvenile justice system with restorative justice and diversion approaches. Legal protection for children includes both preventive and repressive aspects but faces challenges in implementation. The study highlights the importance of government, community, and family roles in preventing and protecting children from online prostitution practices.